História da educação: qual história? - Backes, José Licínio (Revista História da Educação, 2012)
Este artigo reflete sobre uma concepção de história que privilegie uma história da educação que leve em conta as inúmeras diferenças que existem numa sociedade. A partir de Chartier. Busca-se entender que a diferença está para além das da ordem de fortuna (raça, gênero, crença). Junto com este entendimento defende-se também uma história que englobe as vozes marginais, que não absolutize suas verdades e leve em conta que as pessoas não agem/reagem da mesma forma às imposições de uma estrutura, dando espaço para sujeitos singulares e diferentes. Palavras-chave: história da educação, Chrtier, história. Abstract This article reflects about a conception of history which privileges a history of education that considers the innumerous differences existing in society. Departing from Chartier, we try to understand that the difference exists beyond the order of fortune (it includes race, gender, faith). Together with this understanding, we also advocate a history that comprises the marginal voices. which does not consider as absolute its truths and takes into account that different people don’t act/react in the same way to the impositions of a structure, giving space to single and different subjects. Keywords: history of education, Chartier, history.